Gambaran Kematian di RSUP Dr M Djamil Padang - Rahmadiyani, Rahmadiyani; Susanti, Rika; Putri, Biomechy Oktomalio; Manela, Citra; Lestari, Tuti; Rustini, Rini (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The definition of death is stated in the Law of the Republic of Indonesia, this law explains the diagnostic criteria for clinical death and brain stem death. In forensic medicine, we study death, changes after death, and what is behind these changes. Forensic and Medicolegal Department of RSUP Dr. M. Djamil has a body register book which contains data on the deaths of incoming bodies containing name, gender, age, registration number, diagnosis, actions taken and so on. However, there has been no research regarding the alleged cause and manner of death at Dr. M. Djamil Padang. The aim of this study was to determine the description of deaths at RSUP Dr. M. Djamil Padang in 2018-2022. This research is a descriptive study which takes data from the body register book which is entered into the Forensic and Medicolegal Department of RSUP Dr. M. Djamil Padang 2018-2022. The number of bodies entered into the Forensic and Medicolegal Department of RSUP Dr. M. Djamil Padang from 2018 to 2022 is 16,765 bodies. Every year more than 50% of deaths occur in men with the largest age group being the late elderly at 24.2%-25.6% per year and 46.1%-53.1% per year of deaths from West Sumatra outside Padang. The largest group of causes of death based on ICD-10 is the group of symptoms, signs and other disorders at 33%-45% per year with the most frequent diagnoses being septic shock and MODS. Deaths occurring outside hospitals are less than 2% per year. The percentage of unnatural deaths is below 7% per year, of which as many as 40.5%-78.1% per year are not examined because of refusal from the family. Description of death at RSUP Dr. M. Djamil Padang is relatively same every year. Keywords: Forensics, Cause of Death, Description of Death  ABSTRAK Definisi kematian tercantum dalam Undang-Undang Republik Indonesia, yang menjelaskan tentang kriteria diagnosis mati klinis dan mati batang otak. Dalam kedokteran forensik dipelajari tentang kematian, perubahan setelah kematian, dan apa yang melatarbelakangi perubahan tersebut. Departemen Forensik dan Medikolegal RSUP Dr. M. Djamil memiliki buku register jenazah yang berisi data kematian jenazah yang masuk berisi nama, jenis kelamin, usia, nomor registrasi, diagnosis, tindakan yang dilakukan dan sebagainya. Namun, belum ada penelitian terkait dugaan sebab dan cara kematian di RSUP Dr. M. Djamil Padang. Tujuan penelitian ini adalah untuk mengetahui gambaran kematian di RSUP Dr. M. Djamil Padang pada tahun 2018-2022. Penelitian ini adalah penelitian deskriptif dimana mengambil data dari buku register jenazah yang masuk ke Departemen Forensik dan Medikolegal RSUP Dr. M. Djamil Padang tahun 2018-2022. Jumlah jenazah yang masuk ke Departemen Forensik dan Medikolegal RSUP Dr. M. Djamil Padang tahun 2018 hingga 2022 adalah 16.765 jenazah. Setiap tahunnya lebih dari 50% kematian pada laki-laki dengan kelompok usia terbanyak masa lansia akhir sebesar 24,2%-25,6% pertahun dan 46,1%-53,1% pertahun jenazah dari Sumatera Barat diluar Padang. Kelompok penyebab kematian berdasarkan ICD-10 yang terbanyak adalah kelompok gejala, tanda, dan kelainan lainnya sebesar 33%-45% pertahun dengan diagnosis terbanyak syok sepsis dan MODS. Kematian yang terjadi diluar rumah sakit kurang dari 2% pertahun. Persentase mati tidak wajar berada dibawah 7% pertahun, dimana sebanyak 40,5%-78,1% pertahun tidak dilakukan pemeriksaan karena penolakan dari pihak keluarga. Gambaran kematian di RSUP Dr. M. Djamil Padang relatif sama setiap tahunnya. Kata Kunci: Forensik, Penyebab Kematian, Gambaran Kematian